Navigating conflicts of justice in the use of race and ethnicity in precision medicine - Schaefer, G. Owen (Bioethics, 2020)
Given the sordid history of injustices linking genetics to race and ethnicity, considerations of justice are central to ensuring the responsible development of precision medicine programmes around the world. While considerations of justice may be in tension with other areas of concern, such as scientific value or privacy, there are also tensions between different aspects of justice. This paper focuses on three particular aspects of justice relevant to this precision medicine: social justice, distributive justice and human rights. We describe the implications of each for the use of race and ethnicity in precision medicine, and also how they intersect and potentially conflict with each another. By attending to these intersections, we aim to enrich and add nuance to debates over how best to proceed with precision medicine initiatives.